Notes on elementary particle physics - Muirhead, H. (Hugh) (Pergamon Press, 1971)
Notes of Elementary Particle Physics is a seven-chapter text that conveys the ideas on the state of elementary particle physics. This book emerged from an introductory course of 30 lectures on the subject given to first-year graduate students at the University of Liverpool. The opening chapter deals with pertinent terminologies in elementary particle physics. The succeeding three chapters cover the concepts of transition amplitudes, probabilities, relativistic wave equations and fields, and the interaction amplitude. The discussion then shifts to tests of electromagnetic interactions, particul.